1994
DOI: 10.1016/0266-7681(94)90089-2
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the Thumb

Abstract: Thumb duplication is a common congenital abnormality accounting for 6.6% of all hand deformities. The object of the primary surgery is to achieve a thumb with aligned joint surfaces and epiphyses perpendicular to the long axis, central flexor and extensor tendons, and adequate collateral ligaments. Experienced surgeons with an understanding of the abnormal anatomy and knowledge of the numerous refinements in technique cannot guarantee a flawless result. Of 43 cases treated in this Unit during the period 1970-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…4). The same principles and techniques apply to these problems when encountered in any of the other Wassel types, but it is illustrative to detail the techniques used when all elements listed above are deficient in a type IV deformity 3-12)…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…4). The same principles and techniques apply to these problems when encountered in any of the other Wassel types, but it is illustrative to detail the techniques used when all elements listed above are deficient in a type IV deformity 3-12)…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…However, there are differences in the specific proportions of each type reported. The results of this study in southwestern China show that type IV accounts for 39.7% of the affected population, while the proportion reported in another domestic study by Su et al, the Middle East study by Al-Qattan et al, the Japan study by Islam et al, and the UK study by Naasan et al show that type IV accounts for 29.6%, 35%, 33.6%, and 20.9% of the respective populations [ 10 12 ].This is different from our statistical results and may be associated with the sample size. This group of data has a large sample size, similar to the previous reports at home and abroad.…”
Section: Discussionmentioning
confidence: 63%
“…There are 4 surgical methods to approach reconstruction of preaxial polydactyly: (1) simple excision of the duplicated digit, (2) excision of the duplicated digit with reconstruction of the soft tissues, (3) wedge resection of central bone and soft tissue (Bilhaut-Cloquet procedure), and (4) on-top plasty. Simple excision was initially advocated, but subsequent follow-up studies showed unacceptable thumb function and appearance, as it fails to align joint surfaces and epiphyses perpendicular to the long axis of the thumb, centralize the flexor and extensor tendons, and provide adequate collateral ligaments for joint stability 42,46,47 .…”
Section: Preaxial Polydactylymentioning
confidence: 99%